Réponses

2013-10-27T13:31:37+01:00
8x³ + 4x=4x(2x²+1)

8x(x-1)² - 2x(x-1)
=8x(x²-16x+1)-2x²+2x
=8x³-128x²+8x-2x²+2x
=8x³-130x²+10x
=x(8x²-130x+10)
=2x(4x²-65x+5)
Meilleure réponse !
2013-10-27T13:46:16+01:00
Alors pour le premier ; 
8X^3+4X = 4X x (2X²+1)
Avec X l'inconnue et x pour le signe multiplié :)

Et le deuxième :
8X(X-1)²-2X(X-1) = 2X x 4 x (X-1) x (X-1)-2X(X-1)
                          = 2X(X-1) x 4 x (X-1) - 2X(X-1)
                          = (2X(X-1)) (4(X-1)-1)
                          = (2X²-2X) (4X-5)

Avec plaisir ;)
Dadawo.